Implementasi Pembelajaran Konektivisme Berbasis Kolaboratif Melalui Canva - Yessy Septiani Yuono; Nuril Huda; Soesiana Tri Eka (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Connectivism is a learning theory that emphasizes the importance of networks and connections in the learning process, especially in the context of modern digital and technology. Learning is no longer limited to physical classrooms, but involves various sources of information spread through the internet network. In this digital era, tools and applications such as Canva are very relevant. Canva is a graphic design platform that allows users to create a variety of visual content easily and collaboratively. Through connectivism, applications such as Canva allow students to work together on design projects, share ideas, and access various visual resources from all over the world. By using Canva, students not only learn graphic design skills, but also develop the ability to collaborate effectively, access information quickly, and integrate knowledge from various disciplines. This reflects the principles of connectivism where learning occurs through dynamic interactions between learners and technology, creating a richer and more connected learning environment.